Interbank contagion at work: evidence from a natural experiment - Rajkamal Iyer; José-Luis Peydró (European Central Bank (ECB), 2010)
This paper tests financial contagion due to interbank linkages. For identification we exploit an idiosyncratic, sudden shock caused by a large-bank failure in conjunction with detailed data on interbank exposures. First, we find robust evidence that higher interbank exposure to the failed bank leads to large deposit withdrawals. Second, the magnitude of contagion is higher for banks with weaker fundamentals. Third, interbank linkages among surviving banks further propagate the shock. Finally, we find results suggesting that there are real economic effects. These results suggest that interbank linkages act as an important channel of contagion and hold important policy implications.
Keywords: G21; G28; E58; 330; Bank runs; banking crisis; Contagion; Deposit Insurance; Interbank Market; liquidity dry-ups; macro-prudential analysis; systemic risk; wholesale depositors; Bankinsolvenz; Ansteckungseffekt; Geldmarkt; Einlagensicherung; Bankenkrise; Wirkungsanalyse; Gujarat; Indien